Museum Geologi Di Pekanbaru Dengan Pendekatan Arsitektur Modern - Desy Susanti; Pedia Aldy; Muhammad Rijal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Riau Province as one of the largest oil-producing province in Indonesia need a place to take care of and show off the results of the oil. Geological Museum emerged as one solution to showcase the results of the oil, rocks and other mining products. So, people can learn the procedures and results of oil and mining in the province of Riau. The design of geological museum uses modern architecture approach, the museum is applying the characteristics of modern architecture in those architectural aspects such as: (1) mass form; (2) The structure system; (3) facadematerial; (4) The circulation space. Clarity and  Simplicity concept chosen as the basic concept design. Clarity and Simplicity concept is produce a simple design museum and it will make it easier for visitors to see the variousfacilities provided by the geological museum. The results of design applied to geological museum such as zoning, structure, order of mass, mass formation, structure and arrangementof space in outer space. In the shape of building produces a simple building shape and the clearlycirculation will make visitor easier to going around. The design of this geologicalmuseum has 1.3 hectares land area and 1.02 hektares for total building areas.Keywords: Geological Museum, Modern Architecture, Clarity and Simplicity